Efektivitas Permainan Uno Stacko Mission guna Meningkatkan Keterampilan Berbicara Arab Peserta Didik - Syaharani, Jasmine; Syihabuddin, Syihabuddin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The study is set back by its weak speech proficiency in Bandung Junior High School Daarul Adab. 79% of the value of Al-ḥiwār protege is below KKM. Therefore, the study wanted to address the problem by applying Uno Stacko Mission media in Al-ḥiwār studies and to help educators develop the media. To achieve the objectives in question used experimental methods designed by the pretest and posttest control group. This sample of 34 learners is divided into two groups, namely the experimental and control group. A data gathering instrument of proficiency tests that have been validated and reliably tested. The data gathered is prepared using version 28 of the SPSS application. Data analysis shows that the average value of experiment classes is higher (83.71) than the average rate of the control class (75.88). Hypothetically presented with a sig. (2-tailed) 0.034 or indicating an acceptable hypothesis. The conclusion, then, is that the medium of learning, stack, does well in Arabic, especially in Al-ḥiwār material.